PENGETAHUAN PASANGAN USIA SUBUR (ISTRI ) TENTANG INFERTILITAS DI LINGKUNGAN SUKA DAME KELURAHAN URUNG KOMPAS KECAMATAN RANTAU SELATAN KABUPATEN LABUHANBATU TAHUN 2018 - Fitriyani - Nasution (Akademi Kebidanan Ika Bina, 2018)
According to the World Health Organization (WHO) shows that the number of partners of infertility as much as 36% is caused by abnormalities in men, while 64% are in women. This is experienced by 17% of couples who have been married for more than 2 years have not experienced signs of pregnancy and have never been pregnant at all. Difficulty having children due to failure of dysfunction of the reproductive organs in a married couple is known as infertility. Husband and wife couples can be said to be infertile (infertile) if they do not have children in the span of one year from their marriage. This means that sexual relations committed by the couple fail. This study aims to determine the knowledge of fertile age couples (wives) about infertility in the environment like dame, urung kompas village, rantau selatan district, labuhan batu, based on variables of age, education, occupation and sources of information. This study is descriptive, sampling using accidental sampling techniques, with a population of 152 people and obtained 60 samples. This type of research is primary and secondary data. Data collection was conducted on May 30, 2018, using good criteria (68100%), sufficient (34-67%), and less (0-33%). The results showed that of the 60 majority respondents with less knowledge with the number of 26 respondents (43.33%) and the majority were well informed as many as 12 respondents (20.00%). In terms of age, the majority of respondents who were knowledgeable were less than 39-42 years old as many as 11 respondents (18.33%). Based on education, the majority of respondents were less knowledgeable with basic education as many as 17 respondents (85.00%). Based on the work, the majority of respondents with less knowledge were 18 respondents (30.00%) for respondents who did not work. Based on the source of information, the majority of respondents were less knowledgeable as many as 18 respondents (30.00%) to respondents who did not get a source of information.From the results of the research on fertile age couples (wives) about the majority of infertility, they have less knowledge and are expected to the community to improve the quality of life and awareness of health by asking questions and taking the time to get information about health through both print and electronic media and want to attend counseling - counseling held by health workers